A Comprehensive Review of Quality of Life (QOL) Research in Hong Kong - Daniel T. L. Shek; Britta M. Lee (The Scientific World Journal)
Published quality of life (QOL) studies in Hong Kong indexed in the major databases were reviewed. Several observations are highlighted from this review. First, most of the published studies were empirical studies involving data collection. Second, there are more micro studies utilizing individual QOL indices than macro studies using societal indicators. Third, most studies addressed personal well-being, followed by studies on family well-being and societal well-being. Fourth, the studies were predominantly quantitative in nature. Fifth, most of the studies were based on adults and comparatively fewer studies were based on children and adolescents. Sixth, most studies were based on populations with special needs, followed by studies based on the general population, helping professionals, and caregivers. Seventh, most studies used measures of QOL rather than developed QOL measures. Finally, QOL data in Hong Kong were seldom compared with those in other places. The gaps on QOL studies in Hong Kong and future research directions are discussed.